Effect of breed-type on carcass weight and composition in sheep - Gaili, E.S.E. (Springer, 1979)
The relative rate of increase in the carcass and its tissues with increasing empty body weight (EBW) or carcass weight respectively, was studied in male sheep from the Dorset Horn (29), Hampshire (21) and Sudan Desert sheep (31). The rate at which the carcass, muscle and bone increased in weight was the same in all breeds but the Sudan Desert sheep deposited fat at a slower rate than the other 2 breeds. At an equally adjusted EBW the Desert sheep had lighter carcass than the Dorset Horn or Hampshire sheep. Sudan Desert sheep had more bone than the other 2 breeds at an equally adjusted cold carcass weight or muscle plus bone weight. At an equally adjusted total carcass fat weight the Sudan Desert sheep had significantly (p